2018
DOI: 10.2298/sos1803275v
|View full text |Cite
|
Sign up to set email alerts
|

Development of an energy- and water-saving manufacturing technology of brick products

Abstract: In the work, the carrying of realizing three problems in the manufacture of brick products, namely, energy saving, water saving, and processing of large-scale waste (ecological problem), are considered. Four types of bricks have been obtained and investigated: red clay, red clay-milled cullet mixture, red clay-milled basalt (tezontle) mixture, and red clay-milled glass-milled tezontle mixture. To form the semi-finished products, water or wet waste of activated sludge were added to the dry mixtures. It is estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The varied sizes of pores may be generated by the diffusive gas flow emanations (water and carbon dioxide) upon firing specially by the action of transforming clays [30,31]. This high porosity of the ceramics implies the presence of closed and open pores, which are important for the evaluation of the brick products properties [32]. The elemental mapping by EDS revealed that silicium, aluminium and iron are present in higher concentration close to the surface at 1150 o C. This remark is in conformity with the new mineral identified by XRD analysis like mullite, cristobalite and spinel which results from the combination of different ions during the melt process.…”
Section: Microstructure Of Firing Brick 331 Microstructure In Polamentioning
confidence: 99%
“…The varied sizes of pores may be generated by the diffusive gas flow emanations (water and carbon dioxide) upon firing specially by the action of transforming clays [30,31]. This high porosity of the ceramics implies the presence of closed and open pores, which are important for the evaluation of the brick products properties [32]. The elemental mapping by EDS revealed that silicium, aluminium and iron are present in higher concentration close to the surface at 1150 o C. This remark is in conformity with the new mineral identified by XRD analysis like mullite, cristobalite and spinel which results from the combination of different ions during the melt process.…”
Section: Microstructure Of Firing Brick 331 Microstructure In Polamentioning
confidence: 99%
“…Table V shows that P-3 sample has the highest bending strength of 30.54 MPa at 20 wt% of Kalalani vermiculite content when sintered at 1250 o C. This might be due to vitrification and densification which filled the microcracks and voids in the microstructure of the porcelain sample [19]. Therefore, the mechanical properties of ceramic sample are strongly dependent on composition made, the sintering temperature and the sintering time [20]. The results of the study are in agreement with the works of [5,16].…”
Section: Tab IIImentioning
confidence: 99%
“…Since in the given porous ceramics, low-ordered carbon is present, it must possess adsorption properties [12,13]. The performed investigations showed (Fig.…”
Section: Adsorption Properties Of Carbonized Bricksmentioning
confidence: 99%
“…This concerns the development of modern efficient building materials, combining the properties of wall structural, heat-insulating, and sound-insulating materials. Moreover, the production of such ceramics must be based on an energy-and resource-saving technology to provide a substantial reduction in the production costs of bricks and building costs on the whole [10][11][12]. Porous bricks exhibiting sound-and heat-insulating properties are of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation